ANALISIS SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SDN 105316 BERANTI - Paska Sriulina Tarigan; Polintan Rehulina Sembiring; Yenni Florentina Ginting (JURNAL CURERE, 2022)
The duties and responsibilities of the principal's supervision greatly determine the performance of teachers in the school. Supervision is aimed at teaching and learning situations that allow the achievement of educational goals optimally, in improving and improving the quality of teaching. The principal who has responsibilities as a leader, such as being able to show an exemplary personality for teachers and staff, has great expertise in leading a particular school, will know the teacher's performance, such as the teacher will be responsible, disciplined, and enthusiastic. This research uses descriptive research. The purpose of the study was to find out the description of Principal Supervision in improving teacher performance at SDN 105316 Beranti. The population in this study were all teachers at SDN 105316 Beranti, both civil servants and non-civil servants who found 12 people. From the results of this study, it can be said that the supervision of the principal at SDN 105316 Beranti has very good criteria. The better the supervision of the principal, the better the teacher's performance